2016
DOI: 10.21767/2471-8203.100025
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Prevalence of Obesity in Saudi Arabia

Abstract: Over the past 3 decades, the prevalence of overweight and obesity has increased dramatically worldwide. The rising trend of obesity indicates that this increase is not only confined to the developed world, but also extending towards the developing world. In the context, Saudi Arabia is now among the nations with the highest obesity and overweight prevalence rates due to a number of factors. This research explores and evaluates the prevalence of obesity in Saudi Arabia on the basis of the findings of previous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 12 publications
6
144
2
Order By: Relevance
“…Compounding this situation, Al-Hazzaa [10] indicated that the total rate of physical inactivity among Saudi citizens ranged from 43.3% to 99.5%. The prevalence of obesity has also increased among both Saudi adults and children [11]. The Saudi Diabetes and Endocrine Association in 2010 estimated the indirect and direct costs of obesity problems in the KSA population to be about five billion dollars per year [9].…”
Section: Saudi Arabian Healthcare Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounding this situation, Al-Hazzaa [10] indicated that the total rate of physical inactivity among Saudi citizens ranged from 43.3% to 99.5%. The prevalence of obesity has also increased among both Saudi adults and children [11]. The Saudi Diabetes and Endocrine Association in 2010 estimated the indirect and direct costs of obesity problems in the KSA population to be about five billion dollars per year [9].…”
Section: Saudi Arabian Healthcare Systemmentioning
confidence: 99%
“…The Saudi Diabetes and Endocrine Association in 2010 estimated the indirect and direct costs of obesity problems in the KSA population to be about five billion dollars per year [9]. Furthermore, rates of hypertension, hypercholesterolemia, type 2 diabetes, arthritis problems, and cancer have all increased dramatically in recent years among Saudi citizens [11,12]. These unhealthy diets, smoking, lack of sufficient physical activity, chronic viral infections, and lack of knowledge about cancer and its prevention and screening methods have resulted in rising burden of cancer reported as one of the fastest growing health concerns in the KSA [12,13,14,15].…”
Section: Saudi Arabian Healthcare Systemmentioning
confidence: 99%
“…It was also found that 41 million children under the age 5 were overweight or obese (2014), and that most of the world's population live in countries were overweight and obesity kills more people than underweight (WHO, 2015). Alqarni (2016) states that the determinants of obesity include: (1) family history of obesity; (2) diet; (3) marital status; (4) diagnoses of diabetes; (5) physical activity; (6) education; (7) age; (8) hypertension; (9) high glucose level; (10) eating habits; (11) sleeping interruptions; and (12) genetic factors. Alqarni (2016) states that the consequences of obesity include: (1) cardiovascular diseases; (2) cancers; (3) hypertension; (4) hypercholesterolemia; and (5) Ischemic heart disease.…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…Alqarni (2016) states that the determinants of obesity include: (1) family history of obesity; (2) diet; (3) marital status; (4) diagnoses of diabetes; (5) physical activity; (6) education; (7) age; (8) hypertension; (9) high glucose level; (10) eating habits; (11) sleeping interruptions; and (12) genetic factors. Alqarni (2016) states that the consequences of obesity include: (1) cardiovascular diseases; (2) cancers; (3) hypertension; (4) hypercholesterolemia; and (5) Ischemic heart disease. Obesity may also lead to other serious risks such as type 2 diabetes, coronary heart disease, some types of cancer (e.g.…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…[4] Also, many studies conducted among Saudi population showed that according to the body mass index (BMI), obesity has been rising dramatically over the past 30 years due to modernization and the obvious economic growth that affected the life style and resulted in bad dietary habits. [5,6] Also, many studies have proposed the impact of physical activity, dietary habits, food consumption as well as the economic status as modifiable factors on the prevalence of obesity. [7,8] Thus, the present study aimed to estimate the effectiveness of life style on the BMI among Saudi adult population.…”
Section: Introductionmentioning
confidence: 99%